White Farmers Black Land - Lee, Aldo (South Africa, 2000)
Soros Documentary Fund “White Farmers Black Land” explores questions of race and cultural identities while following a group of South African farmers, still traumatized with the changes taking place in their country. In 1994 some white farmers decided to participate in an agricultural development project in Northern Mozambique. But the rich Niassa lands are already occupied by the Yao, who are set against letting these rich Afrikaners grab hold of the lands of their ancestors. This film follows closely Daan Fritz and his family and a few other pioneers as they travel northwards in the footsteps of their Boer ancestors who, two hundred years ago, set out on the Great Trek which has become the founding myth of Afrikaner culture.